2013
DOI: 10.3402/tellusb.v65i0.19822
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and evolution of air quality monitoring networks using combined statistical information indexes

Abstract: A B S T R A C TIn this work, we present combined statistical indexes for evaluating air quality monitoring networks based on concepts derived from the information theory and KullbackÁLiebler divergence. More precisely, we introduce: (1) the standard measure of complementary mutual information or 'specificity' index; (2) a new measure of information gain or 'representativity' index; (3) the information gaps associated with the evolution of a network and (4) the normalised information distance used in clustering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…Many attractive criteria have been proposed: root mean square errors of network-based estimation of the field, information-theoretical based criteria, etc. Such criteria have been investigated in atmospheric chemistry in many studies conducted by environmental statisticians, more recently for instance by Fuentes et al (2007) and Osses et al (2013). Nowadays, the network design issue also concerns the sparse ground networks of greenhouse gas monitoring at mesoscales and global scales (Rayner, 2004;Lauvaux et al, 2012), which in our context can be seen mostly as tracers of atmospheric transport.…”
Section: Optimal Monitoring Network Designmentioning
confidence: 99%
“…Many attractive criteria have been proposed: root mean square errors of network-based estimation of the field, information-theoretical based criteria, etc. Such criteria have been investigated in atmospheric chemistry in many studies conducted by environmental statisticians, more recently for instance by Fuentes et al (2007) and Osses et al (2013). Nowadays, the network design issue also concerns the sparse ground networks of greenhouse gas monitoring at mesoscales and global scales (Rayner, 2004;Lauvaux et al, 2012), which in our context can be seen mostly as tracers of atmospheric transport.…”
Section: Optimal Monitoring Network Designmentioning
confidence: 99%
“…All in all, our results for summer conditions suggest that downtown stations are important from the point of view of total information content regarding CO. A previous study that considered multiple species using statistical information indexes by Osses et al (2013) also suggested retention of downtown stations. These stations were in fact deemed to be the most representative of dispersion patterns for the Santiago basin, considering all species and all hours of the day, and all seasons of the year.…”
Section: Reduction Of the Networkmentioning
confidence: 99%
“…We further address the evolution of the air quality network in terms of its information gain by taking into account both the number and the location of CO stations. We discuss the pros and cons of the variational approach introduced here and compare it with the results of a statistical approach previously presented by Osses et al (2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations